Automatic Orientation of Multi-Scale Terrestrial Images for 3D Reconstruction - Tommaselli, Antonio M. G. [UNESP]; Berveglieri, Adilson [UNESP] (Mdpi Ag, 2014)
Image orientation requires ground control as a source of information for both indirect estimation and quality assessment to guarantee the accuracy of the photogrammetric processes. However, the orientation still depends on interactive measurements to locate the control entities over the images. This paper presents an automatic technique used to generate 3D control points from vertical panoramic terrestrial images. The technique uses a special target attached to a GPS receiver and panoramic images acquired in nadir view from different heights. The reference target is used as ground control to determine the exterior orientation parameters (EOPs) of the vertical images. These acquired multi-scale images overlap in the central region and can be used to compute ground coordinates using photogrammetric intersection. Experiments were conducted in a terrestrial calibration field to assess the geometry provided by the reference target and the quality of the reconstructed object coordinates. The analysis was based on the checkpoints, and the resulting discrepancies in the object space were less than 2 cm in the studied cases. As a result, small models and ortho-images can be produced as well as georeferenced image chips that can be used as high-quality control information.
Keywords: close range; large-scale surveying; target detection; 3D point